Sonate für das Piano-Forte von L. van Beethoven. Op. [31 No. 3]. Neue correcte Ausgabe. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Frankfurt am Main; Jos. Ant. Löhr; Germany, 2022)
Edition of Beethoven's Piano Sonata no. 18 in E-flat major, op. 31, no. 3, published ca. 1830-1835 by Jos. Ant. Löhr in Frankfurt am Main as part of a series of "neue correcte Ausgabe(n)" (new correct editions).